Withstanding the Challenges on Infantry Operational Courses: The Case of Military Women in the Division Training School in Cotabato City - Wilter Friales; Catherine Rolluqui; Marianne Daphne Villahermosa; Sittie Noor Ohara Karon (East Asian Journal of Multidisciplinary Research, 2023)
Withstanding military training by women is the phenomenon of this research; hence, the study explores and presents women’s coping mechanisms in dealing with challenges. The study was conducted through the lens of psychological resilience theory. The study aimed to gained insights into the experiences of military women on how they withstood the challenges during their training under the Infantry Operational Courses. Specifically, this study answered the questions on how do they describe their challenges and how they cope with the challenges in the training using a Qualitative Case Study approach. The participants  were the 5 chosen military women who withstood and passed the Infantry Operational Course in the Military Training School in Cotabato City whose names and identity were kept confidential. As a result,The challenges encountered by the participants are represented by the following themes: (1) discipline and self-control, (2) obedience, (3) personal feminine hygiene deficiency, (4) stringent physical, mental, & psychological training, (5) mental stress, (6) social stress, (7) missing one’s family, (8) longing for personal wants and feminine lifestyle, (9) reproductive system problems and diseases. Five themes emerged from the analysis of the significant statements of the participants of the study; These themes on coping mechanisms are the following: (1) Praying and having faith in God; (2) Internal motivation; (3) Drive; (4) Submissiveness; and (5) Social Support.